2016
DOI: 10.1016/j.celrep.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Engages AGO2 to Enhance Cellular Transformation

Abstract: SUMMARY Oncogenic mutations in RAS provide a compelling yet intractable therapeutic target. Using co-immunoprecipitation mass spectrometry, we uncovered an interaction between RAS and Argonaute 2 (AGO2). Endogenously, RAS and AGO2 co-sediment and co-localize in the endoplasmic reticulum. The AGO2 N-terminal domain directly binds the Switch II region of KRAS, agnostic of nucleotide (GDP/GTP) binding. Functionally, AGO2 knockdown attenuates cell proliferation in mutant KRAS-dependent cells, and AGO2 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 68 publications
5
70
0
Order By: Relevance
“…2 h after microinjection, l7-Cy5/l7* in live cells had again assembled into slowly diffusing RNPs (Figures 2A and 2B), which together with corresponding reporter gene assays (Figure 2C) indicated that l7 loaded RISC binds to and actively represses target mRNAs (Pitchiaya et al, 2012; Pitchiaya et al, 2013; Shankar et al, 2016). Strikingly, microinjecting an equivalent quantity of single-stranded (ss) l7 (l7-Cy5) resulted in similarly diffusing complexes, however, the (normalized) number of such particles was significantly (~3-fold) less than for l7-Cy5/l7* (Figures 2A and 2B).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…2 h after microinjection, l7-Cy5/l7* in live cells had again assembled into slowly diffusing RNPs (Figures 2A and 2B), which together with corresponding reporter gene assays (Figure 2C) indicated that l7 loaded RISC binds to and actively represses target mRNAs (Pitchiaya et al, 2012; Pitchiaya et al, 2013; Shankar et al, 2016). Strikingly, microinjecting an equivalent quantity of single-stranded (ss) l7 (l7-Cy5) resulted in similarly diffusing complexes, however, the (normalized) number of such particles was significantly (~3-fold) less than for l7-Cy5/l7* (Figures 2A and 2B).…”
Section: Resultsmentioning
confidence: 85%
“…Yet, little is known about their spatiotemporal distribution and functionality within their native cellular environment. To bridge this gap, we here have refined our single-cell, single-molecule iSHiRLoC approach (Pitchiaya et al, 2012; Pitchiaya et al, 2013; Shankar et al, 2016) and applied it to mechanistically probe the miRNA-induced cytoplasmic RNA silencing pathway and its non-canonical nuclear counterpart. First, we validated our previous findings on the intracellular assembly of miRNAs (Pitchiaya et al, 2012), developed and validated a correlative live- and fixed-cell counting analysis to probe miRNA stability and function, and extended the applicability of iSHiRLoC to a wider range of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, photobleaching event counting holds the promise to quantify release of DDS cargo more accurately (Pitchiaya et al. , 2012, 2013, 2014; Shankar et al. , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…, 2012, 2014, 2013; Shankar et al. , 2016), using a home-built IX-81 Olympus microscope with a 60×, 1.49 numerical aperture oil immersion objective (Olympus, Lombard, IL), 2× magnification wheel, P–545.3C7 capacitive piezoelectric xyz -stage (Physik Instrumente, Karlsruhe, Germany), iXon 897 (Andor, Belfast, United Kingdom) electron-multiplying charge-coupled device camera, and a Cell-TIRF module (Olympus).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate potential additional modulators of RAS-mediated oncogenesis, we previously performed a screen for direct interactors of RAS in a panel of cancer cell lines and identified a direct interaction between KRAS and Argonaute 2 (AGO2), independent of KRAS mutation status 15 . The N-terminal domain of AGO2 was found to bind the regulatory Switch II region in RAS and was required for oncogenic KRAS-driven cellular transformation.…”
Section: Introductionmentioning
confidence: 99%